Analisis Perbandingan Kinerja Simulator NIBP Impor dan Lokal terhadap Blood Pressure Monitor dengan Metode Uncertainty - Safariati Isabela; Eka Nuryanto Budisusila (MEDIKA TRADA, 2025)
Calibration of non-invasive blood pressure (NIBP) devices is essential to ensure measurement accuracy in healthcare services. This study aims to compare the performance of two calibrators, XB1000 and Multisim, in testing two NIBP units using the uncertainty analysis method. Measurements were conducted on systolic, diastolic, and heart rate parameters with a total of 16 data points per parameter. The results show that XB1000 achieved a lower total average expanded uncertainty (U95) of 0.421 mmHg compared to Multisim at 0.529 mmHg. Specifically, XB1000 demonstrated the lowest uncertainty across all parameters, with an overall 20.3% improvement over Multisim. Error analysis indicated that systolic measurements had an average error of 2.063 mmHg, diastolic -1.167 mmHg, and heart rate -0.062 bpm. Based on these findings, XB1000 is recommended as the preferred calibrator for NIBP devices, as it provides lower measurement uncertainty and improved accuracy across all tested parameters.